Read with Me: Celebrating our Local Literacies - Peñaloza Rallón, Anna Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The following literary works were presented at the "Read with me: Celebrating our Local Litercies" eventheld by Enletawa Journal on August 27, 2021. When discussing literacy, Freire gave us a look at the depth ofthe concept when he said, "If we think of education as an act of knowing, then reading has to do withknowing. The act of reading cannot be explained as merely reading words since every act of reading wordsimplies a previous reading of the world and a subsequent rereading of the world" (1986, p. 18). Therefore,literacy is much more than the act of reading and writing words. It is the act of conciously reading theWorld. If litercy involves reading the World, then it also includes understanding our history and culture, andif possible, contributing to its negotiation and transformation. As Nieto-Gómez and Clavijo-Olarte (2020)mentioned, "Teachers and students can become researchers that use language to question and produce textsinformed by their own reality" (p. 31). Hence, literacy gives us the power to become creators of our ownWorld.